Large range sizes link fast life histories with high species richness across wet tropical tree floras - Timothy R. Baker; Stephen Adu-Bredu; Kofi Affum-Baffoe; Shin-ichiro Aiba; Perpetra Akite; Miguel Alexiades; Everton Almeida; Edmar Almeida de Oliveira; Esteban Alvarez Davila; Christian Amani; Ana Andrade; Luiz Aragao; et al. (Scientific Reports)
Abstract Understanding how the traits of lineages are related to diversification is key for elucidating the origin of variation in species richness. Here, we test whether traits are related to species richness among lineages of trees from all major biogeographical settings of the lowland wet tropics. We explore whether variation in mortality rate, breeding system and maximum diameter are related to species richness, either directly or via associations with range size, among 463 genera that contain wet tropical forest trees. For Amazonian genera, we also explore whether traits are related to species richness via variation among genera in mean species-level range size. Lineages with higher mortality rates—faster life-history strategies—have larger ranges in all biogeographic settings and have higher mean species-level range sizes in Amazonia. These lineages also have smaller maximum diameters and, in the Americas, contain dioecious species. In turn, lineages with greater overall range size have higher species richness. Our results show that fast life-history strategies influence species richness in all biogeographic settings because lineages with these ecological strategies have greater range sizes. These links suggest that dispersal has been a key process in the evolution of the tropical forest flora.